Novel multi-cationic imidazolium and benzimidazolium based ionic liquids: Synthesis and applications for antibacterial and biodegradable surfactants / Nassir N. N. Hassun Al-Mohammed - Nassir N. N., Hassun Al-Mohammed (2016)

(untitled)
Ionic liquids as neoteric compounds exhibit many interesting properties, which make them suitable for broad practical applications of industrial and medical applications. Therefore, in current thesis work several novel series of di, tri and tetra-cationic ionic liquids based on imidazolium and benzimidazolium were synthesized simply from readily available starting materials in high yield. Their structures were confirmed by 1H-NMR, 13C-NMR, FT-IR, and high resolution mass spectroscopy as well as 19F-NMR when necessary. Variations of the synthesized ionic liquid molecular structures led to different applications in life science. The antibacterial activities of bis-imidazolium and benzimidazolium ionic liquids were screened against standard strains of Gram positive and Gram negative bacteria using the micro-broth dilution assay. Most of the studied di-cationic ionic liquids showed promising activities against both types of bacteria due to their high solubility in water in addition to incorporating to sulphonamide moiety. Biodegradability and surfactants properties of tris and tetrakis for both imidazolium and benzimidazolium ionic liquids were investigated. ‘Closed-Bottle Test’ OECD 301D with sodium n-dodecyl sulphate (SDS) as a reference, optical polarizing microscopy and systematic surface tension measurements of aqueous solutions were used for evaluation of their physical behaviour. Some ionic liquids showed assembly behaviour in pure form (i.e. absence of solvent) and in the presence of polar or nonpolar solvents. These surfactants of both imidazolium and benzimidazolium ionic liquids effectively reduced the surface tension of water in the range of 28–34 mN m‒1. The incorporation of tri- and tetra alkyl or phenyl side chains into imidazolium and bezimidazolium ionic liquids with tri and tetra-ester groups, significantly improved the biodegradation. The linear alkyl side chains (i.e. butyl, hexyl, octyl, decyl and dodecyl) in both imidazolium and benzimidazolium ionic liquids series promoted an increase in biodegradation and phase behaviour results as compared to aromatic side-chains.